The Horrors of being single: an intrapersonal and interpersonal phenomenon - Adelson, Sarah K. (My University, 2016)
The present research builds off of previous findings regarding the Fear of Being Single construct (FOBS) indicating that people with higher FOBS scores discriminate less between potential dating partners who show little or high responsiveness to being in a serious relationship. Previous research was expanded in the current study by incorporating interpersonal items to the FOBS scale, which previously contained only intrapersonally focused items. Participants were primed with either unconditional social acceptance or a control using a written visualization task, with the expectation that higher social acceptance will buffer the effect of FOBS (i.e., socially affirmed participants will show more discrimination between targets compared to the control condition). Heterosexual, undergraduate women (N = 127) completed a revised version of the FOBS scale as part of a prescreening process. Participants were randomly assigned to either a high acceptance visualization condition or a control visualization condition and then randomly assigned to read a dating profile depicting either a high responsiveness or a low responsiveness target. Specific predictions include a main effect of responsiveness condition among low FOBS participants only, such that more romantic interest will be shown in the high responsiveness profile than in the low responsiveness profile because participants will not face anxiety at the thought being single rather than date an unresponsive partner. Also predicted was an interaction of responsiveness and visualization condition for high FOBS participants only, such that less romantic interest will be shown for both profiles in the unconditional acceptance condition, with especially low romantic interest shown in the unconditional acceptance/high responsiveness profile condition, due to a buffering effect of the unconditional acceptance prime. Finally, a greater amount of variance was expected to be explained of these relationships when using the revised FOBS scale compared to the original FOBS scale, because the revised scale included socially-relevant items and because FOBS is conceptualized as a socially-relevant fear. Results show that profile manipulation significantly influenced romantic interest (i.e., less romantic interest was shown for the low responsiveness profile than the high responsiveness profile). The profile manipulation significantly interacted with visualization manipulation: less romantic interest was shown for the profile in the unconditional visualization/ high responsiveness profile condition than in the control visualization/high responsiveness profile condition, more romantic interest was shown in the control visualization/high responsiveness profile manipulation than in the control visualization/low responsiveness profile manipulation, and more romantic interest was shown for the profile in the unconditional visualization/high responsiveness profile condition than in the unconditional visualization/low responsiveness profile condition. Additional findings and implications are discussed.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science in Psychology Cognitive Affective
Keywords: Living alone; Lifestyles; Mate selection; Single people